Changing characteristics of rotavirus diarrhea in children younger than five years in urban Bangladesh. - Mohammad Habibur Rahman Sarker; Sumon Kumar Das; Shahnawaz Ahmed; Farzana Ferdous; Jui Das; Fahmida Dil Farzana; Abu S M S B Shahid; K M Shahunja; Mokibul Hassan Afrad; Mohammad Abdul Malek; Mohammod Jobayer Chisti; Pradip Kumar Bardhan; et al. (PLoS ONE, 2014)
BACKGROUND: Childhood rotavirus diarrhea is still one of the major public health challenges. The present study aimed to determine changing characteristics of rotavirus diarrhea in under-5 children at two periods of time. METHODS: We enrolled 5,357 under-5 children with rotavirus positive in two different time periods; i) 1993-1997 (n = 2,493), and ii) 2008-2012 (n = 2,864) considering beginning and ending of two decades. These children were enrolled in the urban Dhaka Hospital of icddr,b. RESULTS: Overall, proportion of rotavirus was about 25% in 1993-97, which was 42% in 2008-12 (68% rise; p<0.001). Significant higher proportion of children were stunted [38% vs. 22%; aOR-1.33 (95% CI-1.09-1.62)], had vomiting [87% vs. 74%; aOR-2.58 (95% CI-2.02-3.28)], fever [10% vs. 8%; aOR-1.31 (95% CI-0.96-1.78)], family members >5 [38% vs. 35%; aOR-1.32 (95% CI-1.10-1.58)] required more intravenous fluid [9% vs. 3%; aOR-4.93 (95% CI-3.19-7.63)], had higher co-infection with Shigella [3% vs. 1%; aOR-3.36 (95% CI-1.61-7.03)], Vibrio cholerae [4% vs. 1%; aOR-3.70 (95% CI-2.12-6.46)]; and ETEC [13% vs. 7%; aOR-2.21 (95% CI-1.65-2.97)]; however, significantly lower proportion of them used sanitary toilets [54% vs. 78%; aOR-0.66 (95% CI-0.54-0.80)], boiled drinking water [16% vs. 38%; aOR-0.60 (95% CI-0.48-0.74)], used antimicrobial at home [63% vs. 82%; aOR-0.56 (95% CI-0.46-0.69)] and had some or severe dehydration [18% vs. 34%; aOR-0.15 (95% CI-0.12-0.20)] in 1st observation period compared to that of 2nd. CONCLUSION: Proportion of episodes of under-5 rotavirus diarrhea increased over the period. Concomitant changes in host, socio-demographic and clinical characteristics, and co-infections were also observed. Thus, vaccination campaign which is prevailing in private sector should also be introduced in public sector.